HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS PAMATANG SILIMAHUTA KABUPATEN SIMALUNGUN TAHUN 2017 - Eka Saudur Sihombing; Rohanta Manihuruk (Elisabeth Health Jurnal, 2018)
Exclusive breastfeeding is the first, main and best food for a natural baby. Asi contains various nutrients needed in the process of growth and development of babies. ) The efficacy of breast milk is so large as breast milk can reduce the risk of babies suffering from various diseases. If the baby is sick it will heal faster when getting breast milk. Breast milk also helps the growth and development of children's intelligence Goals: The aim of the study was to determine the relationship between family knowledge and support for mothers with exclusive breastfeeding. Methods: The research method used an analytical survey type with a cross sectional approach to 75 breastfeeding mothers who had babies aged 7-24 months. Data analysis was performed by univariate analysis to obtain an overview of each independent and dependent variable. Data will be presented in the form of distribution, frequency and bivariate analysis to determine whether there is a relationship between independent variables (categorical) and independent variables (categorical) using Chi Square Test. Results: The results of the study obtained the frequency distribution of respondents with good knowledge 45 people (60%), less knowledge of 30 people (40%), family support 33 respondents (44%), family support 42 respondents (56%), ASI actions Exclusive 17 respondents (22.7%), did not provide exclusive breastfeeding 58 respondents (77.3%). There is no relationship between mother's knowledge of exclusive breastfeeding (p-value 0.063). There is no relationship between family support for exclusive breastfeeding p = 0.063 and p = 0.098 (α = 0.05) means that there is no relationship between knowledge and family support for mothers with exclusive breastfeeding. Conclusion: It is recommended to the community especially to mothers and families to increase exclusive breastfeeding so that the baby's needs for breastfeeding are met, and the family continues to provide support for the mother to give the baby exclusive breastfeeding, further researchers use different and varied variables and dig deeper into the mother's attitude towards exclusive breastfeeding with direct interviews with nursing mothers.